Communication Strategy for Dissemination of Information on Blora Kuncara Application in Blora Regency - Tatik Yuniarti; Ahmad Agus Salim (COMMUNICATION MAJOR, 2022)
The Blora Kuncara application is part of the implementation of the Blora Regency smart city program. The app has been downloaded 500 times. But the number of downloaders is still far away with the number of productive people aged 15-65 years which amounted to 587,130 inhabitants in 2018. Therefore, this study aims to determine the communication strategy of the Communication and Informatics Service of Kabupeten Blora in disseminating information about the Blora Kuncara application to the public. The theory used is a communication planning model by Philip Lesly that divides planning into two actions, namely the organization that drives the activity and the public that is the target of the activity. The method used is descriptive qualitative with data collection techniques with interviews, observations, and documentation. The results showed that the communication strategy used by the Communication and Informatics Service of Blora Regency in the dissemination of the Blora Kuncara application was through direct communication, mass media (radio, internet) and through social media. Direct communication used is through socialization activities and special events. The dissemination of information through the internet is carried out through government websites and online news media. The spread through social media is carried out through Facebook, Instagram, Twitter, and Youtube. Social media is used because it is more effective and efficient in disseminating information to the public. Based on the results of the study, it is recommended that local governments can streamline social media in dissemination activities of information to the public. However, collaboration with the mass media is also still carried out to increase public trust.Keywords: Blora Kuncara Application; Communication Strategy; Blora Distric; Dissemination Information; Communication Planning Model